Respuesta :

Answer:

C)h(x) = x-3

Step-by-step explanation:

To find the inverse of a function, switch the "x" and "y" values, then isolate for "x".

f(x) is the y value.

y = x + 3

x = y + 3   Switch x and y

x - 3 = y     Subtract 3 from both sides to isolate

y = x - 3   Change back to function of h

h(x) = x - 3

Answer:

Step-by-step explanation:

hello :

note : g is the inverse of g : f0g = g0f = x

answer : C  the inverse is : g(x) = x-3 because : (f0g)(x) = f(g(x))=f(x-3) = (x-3) +3 = x

and (g0f)(x) =g(f(x)) = g(x+3) = (x+3) - 3 = x